Molecular docking studies of phytochemicals from Curcuma longa against trehalose-6-phosphate phosphatases of pathogenic microbes - Johari, Nurul Anis; Azmihan, Adam; Abdullah, Mohamad Zakkirun; Bakar, Latifah Munirah (Malaysian Institute of Chemistry, 2024)
Trehalose-6-phosphate phosphatases (TPP) are crucial enzymes used by pathogenic microbes for trehalose sugar biosynthesis, which is later beneficial for infection and proliferation. Therefore, inhibition of TPP proteins becomes the main focus for combating pathogenic microbial infection. This study aims to investigate the binding interactions between selected phytochemicals from Curcuma longa against TPP enzymes regarding the binding affinities and the presence of non-covalent interactions using molecular docking software. Molecular docking of C. longa phytochemicals against TPP was performed utilizing various software, including PyMol, Discovery Studio Biovia 2021, AutoDock Vina, and AutoDock Tools version 1.5.7. In silico molecular docking analysis using AutoDock Vina was done to predict the binding energy and interactions of 30 ligands that belong to C. longa with TPP proteins from Cryptococcus neoformans (PDB: 5DX9), Candida albicans TPP C-terminal domain (PDB: 5DXI) and TPP from Salmonella typhimurium in complex with trehalose (PDB: 6UPD), whereas ampicillin, fluconazole and isoniazid act as the drugs control. The three-dimensional (3D) models of TPP docked with 30 phytochemicals revealed that most of them have good binding affinities to the TPP enzyme. Interestingly, anthraquinones exhibited among the highest binding affinities, ∆G: -8.4, -8.1 and -7.5 kcal/mol. In addition, quercetin is one of the ligands that exhibit the strongest binding affinity, which is -9.3 kcal/mol interaction between TPP from C. neoformans, and affinity binding of -7.3 and -6.2 kcal/mol interaction with TPP from C. albicans and S. typhimurium respectively. These findings suggest that turmeric phytochemicals have some potential to act as TPP inhibitors, which could contribute toward the future development of new drugs against TPP-producing pathogenic microbes. The data presented warrant validation using in vitro and in vivo assays.